Distribution of cardiovascular disease risk factors between hypertensive and normotensive adults in Garissa County, Kenya - Osman, Abdihakim M.; Kimani, Harun M.; Gitahi, Mary W. (International Journal Of Community Medicine And Public Health, 2024)
Background: Cardiovascular diseases (CVDs) are diseases affecting the heart and the blood vessels. Globally hypertension is the leading cause of cardiovascular disease and premature death, affecting 26% of the world population with prevalence expected to rise to 29% by 2025. The main study outcome was the distribution of cardiovascular disease risk factors. Secondary outcomes were the knowledge and socio-economic factors and their impact on distribution of cardiovascular disease risk factors. Methods: This was a retrospective case control study. Information regarding the sociodemographic, cardiovascular disease risk factors, knowledge and socioeconomic factors were collected from 140 adult patients (70 hypertensives and 70 normotensives) seeking outpatient services in Garissa County, Kenya. The 95% confidence limit was used and findings whose p≤0.05 was considered statistically significant. Results: Majority of the participants were aged >65 years (28.6%), followed by 56-65 years (24.3%) with a range of 25-75 years and were mainly male (57.1%), had attained at least a primary school education level (39.3%) and employed (53.6%). The prevalence of increased cardiovascular disease risk factors (>3 CVD risk factors) was 72.1% among the study participants with the hypertensive arm having 14.9% higher prevalence. There was statistically significant association between BMI and knowledge with distribution of cardiovascular disease risk factors (p=0.01) and (p=0.05) respectively. Conclusions: The hypertensive arm had marginally higher cardiovascular disease risk factors. High BMI and low knowledge were both associated with increased cardiovascular disease risk factors. Prospective studies with larger sample size and encompassing more counties are recommendable.